Greening the Internet of Things: A Comprehensive Review of Sustainable IoT Solutions from An Educational Perspective - Tuka Kareem Jebur (Indonesian Journal of Educational Research and Technology, 2023)
Green IoT, or the use of Internet of Things (IoT) technologies to promote sustainability and reduce environmental impact, has gained increasing attention in recent years. This paper provides a comprehensive review of the existing research on Green IoT, exploring different approaches to reduce the carbon footprint of IoT devices and networks, including energy-efficient hardware and software design, renewable energy sources, and IoT-based solutions for environmental monitoring and management. The paper discusses the benefits and challenges of using solar, wind, and other renewable energy sources in IoT applications, as well as the use of sensors, data analytics, and machine learning to optimize resource usage and monitor environmental conditions. The key findings of this paper indicate that Green IoT has the potential to play a significant role in addressing environmental challenges, such as climate change and resource depletion. However, there are still many challenges that need to be addressed, including the high cost of renewable energy sources and the complexity of managing large-scale IoT networks. Overall, this paper emphasizes the importance of Green IoT and the need for further research to develop more efficient and sustainable IoT solutions.